Retention and Molecular Evolution of Lipoxygenase Genes in Modern Rosid Plants - Chen, Zhu; Chen, Danmei; Chu, Wenyuan; Zhu, Dongyue; Yan, Hanwei; Xiang, Yan (Frontiers in Genetics, 2016)
ABSTRACT Whole-genome duplication events have occurred more than once in the genomes of some rosids and played a significant role over evolutionary time. Lipoxygenases (LOXs) are involved in many developmental and resistance processes in plants. Our study concerns the subject of the LOX gene family; we tracked the evolutionary process of ancestral LOX genes in four modern rosids. Here we show that some members of the LOX gene family in the Arabidopsis genome are likely to be lost during evolution, leading to a smaller size than that in Populus, Vitis and Carica. Strong purifying selection acted as a critical role in almost all of the paralogous and orthologous genes. The structure of LOX genes in Carica and Populus are relatively stable, whereas Vitis and Arabidopsis have a difference. By searching conserved motifs of LOX genes, we found that each sub-family shared similar components. Research on intraspecies gene colinearity show that recent duplication holds an important position in Populus and Arabidopsis. Gene colinearity analysis within and between these four rosid plants revealed that all LOX genes in each modern rosid were the offspring from different ancestral genes. This study traces the evolution of LOX genes which have been differentially retained and expanded in rosid plants. Our results presented here may aid in the selection of special genes retained in the rosid plants for further analysis of biological function.